The insecurity of Vale’s dams in Minas Gerais, Brazil: applying activity theory to disaster analysis - Botelho, Marcos Ribeiro; Vilela, Rodolfo Andrade de Gouveia; Beltran, Sandra Lorena; Almeida, Ildeberto Muniz de [UNESP]; Querol, Marco Antonio Pereira (FapUNIFESP (SciELO), 2023)
The objective of this article is to point out hypotheses of contradictions historically incubated in Vale’s activity systems and that may have led to Brazil’s biggest environmental disaster, the B I dam break in Brumadinho, and the interdiction of many other dams owned by Vale in the state of Minas Gerais, Brazil. This is a case analysis from secondary data available in interviews, documents, and texts published in different media between 2011 and 2021. We try to demonstrate, from the Historical-Cultural Theory of Activity, the contradictions verified in and between Vale’s activity systems, since the company distributed large dividends to its shareholders, remunerated its directors as never before, reduced costs in relation to incomes, and brutally reduced internal debt, but keeping insufficient investments in dam management, culminating with the break of B I in 2019 and with 29 dams interdicted in March 2021. Financialization has become central to the company’s operations. This study points to a methodological path of the interdisciplinary dialogue to help clarify how strategic managerial decisions, especially those of financial management, could influence the production, maintenance, and safety management of tailings dams.
A insegurança das barragens da Vale em Minas Gerais, Brasil: aplicação da teoria da atividade à análise de desastres
Keywords: Dam Break; Financialization; Mining; Occupational Accident